2021
DOI: 10.1101/2021.01.23.21249554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The longest persistence of viable SARS-CoV-2 with recurrence of viremia and relapsing symptomatic COVID-19 in an immunocompromised patient – a case study

Abstract: BackgroundImmunocompromised patients show prolonged shedding of SARS-CoV-2 in nasopharyngeal swabs. We report a case of a prolonged persistence of viable SARS-CoV-2 associated with clinical relapses of COVID-19 in a lymphoma patient.MethodsNasopharyngeal swabs and blood samples were tested for SARS-CoV-2 by Real time-PCR (RT-PCR). On five positive nasopharyngeal swabs, we performed viral culture and next generation sequencing. We analysed the patients’ adaptive and innate immunity to characterize T and NK cell… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Compared to the receptor binding domain, the NTD initially attracted much less attention. Subsequently, however, multiple substitutions associated with variants of concern and observed in immunocompromised individuals with extended COVID-19 disease were identified in the NTD 2,35,36 . To evaluate potential functional effects of the inserts in the NTD, we mapped them onto the protein structure.…”
Section: Insertions In the S Protein Produce Putative Antibody Escape Variantsmentioning
confidence: 99%
“…Compared to the receptor binding domain, the NTD initially attracted much less attention. Subsequently, however, multiple substitutions associated with variants of concern and observed in immunocompromised individuals with extended COVID-19 disease were identified in the NTD 2,35,36 . To evaluate potential functional effects of the inserts in the NTD, we mapped them onto the protein structure.…”
Section: Insertions In the S Protein Produce Putative Antibody Escape Variantsmentioning
confidence: 99%
“…Besides, SARS-Co-V-2 was not detected in the air of patients' rooms in a study by Sean Wei Xiang Ong (Ong et al 2020).3.2 Results of surfaces and fomites sampling Many studies on the airborne transmission of the SARS-CoV-2 have used the RT-PCR test for diagnosis. Nevertheless, the RT-PCR test detects only SARS-CoV-2 RNA, not the viable or infectious form of virus (Sepulcri et al 2021). Therefore, this technique cannot express the infectious ability of the virus (Ram et al 2021).…”
Section: Results Of Indoor Air Samplingmentioning
confidence: 99%
“…Until autumn 2020, SARS-CoV-2 genetic diversity was most often deemed to be low, as reported in the study of 27,977 SARS-CoV-2 genomes from 84 countries [ 37 ] or in analyses suggesting that the diversity in the surface glycoproteins of influenza A viruses was 437-fold greater than that measured in the SARS-CoV-2 spike [ 38 ]. Thereby, the rapid emergence of several SARS-CoV-2 strains with increased number of mutations, particularly in the spike-encoding gene, that has been reported in some recent observations [ 13 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] ( Table 1 ) questions whether an event (e.g., genetic or ecologic) has occurred that may have modified the virus replication process or the host-dependent virus selection to promote and spread variant viruses that are more transmissible than the previously-circulating strains and capable of escaping immune responses in some cases [ 30 , 32 , 39 ]. It raises fears of an over-amplification of the pandemic worldwide.…”
Section: Emergence Of Sars-cov-2 Variants Harboring Critical Amino Acid Substitutions and Deletion In The Spike Proteinmentioning
confidence: 99%
“…A second hypothesis to explain the emergence and selection of new SARS-CoV-2 variants, the interventionist therapy hypothesis, is linked to the selective pressure of treatments. In order to treat severe COVID-19, some patients received immunoglobulin-based immunotherapy with hyper-immune sera from convalescent COVID-19 patients [ 13 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 61 ] ( Table 1 ). However, a study reported that, of the sera from 26 patients who recovered from COVID-19 and exhibited high titers of anti-SARS-CoV-2 immunoglobulins, only three effectively blocked the binding of the SARS-CoV-2 spike protein to ACE2 [ 62 ].…”
Section: Selection Of Highly Transmissible Variants: ‘Interventionist Therapy Hypothesis’mentioning
confidence: 99%
See 1 more Smart Citation